2001
DOI: 10.1079/phn2001187
|View full text |Cite
|
Sign up to set email alerts
|

The North/South Ireland Food Consumption Survey: the dietary fibre intake of Irish adults

Abstract: Objective: Mean daily intakes of dietary fibre (DF, Southgate) and non-starch polysaccharide (NSP, Englyst) are estimated in a representative sample of adults aged 18-64 years in Ireland. The contribution of food groups to DF and NSP intake is reported and fibre intakes are compared with dietary recommendations and with intakes in some European countries. Design: Food consumption was estimated using 7-day food diaries for a representative sample (n = 1379; 662 men, 717 women) of 18-64 year old adults in the Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 14 publications
3
27
1
1
Order By: Relevance
“…With the exception of studies which used weighed records (83) or a mixed approach (81) , most studies estimated portion size using photographs (30,46,91) , household measures and objects (e.g. cups, spoons, etc.)…”
Section: Diet Records/diet Diariesmentioning
confidence: 99%
See 3 more Smart Citations
“…With the exception of studies which used weighed records (83) or a mixed approach (81) , most studies estimated portion size using photographs (30,46,91) , household measures and objects (e.g. cups, spoons, etc.)…”
Section: Diet Records/diet Diariesmentioning
confidence: 99%
“…From the sourced articles, fifty-one pan-European studies in total were identified: thirty-five named projects and sixteen smaller projects (48,54,56,65,69,72,82,83,88,93,94,107,109,113,114,116) . Most studies assessed dietary intake of F&V among adults (18,41,44,46,48,50,51,(54)(55)(56)(57)59,60,(64)(65)(66)68,69,71,72,(75)(76)(77)(78)(79)(81)(82)(83)(84)86,88,(92)(93)(94)107,…”
Section: Public Health Nutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…These goals for Fe intake have tended to be lower than those set in North America and more in line with those recently updated in the Nordic Nutrition Recommendations (33) , which were used in the present evaluation. Assessment of other micronutrients and specific fatty acids provided by food patterns based on Ireland's national food guide were beyond the scope of the present evaluation, which focused on micronutrients identified as problematic in recent national surveys (17)(18)(19)(20)(27)(28)(29) .…”
Section: Discussionmentioning
confidence: 99%